Development and evaluation of an Android-based multimedia application to promote healthy lifestyles in physical education: A study at State Junior High School 29 Semarang - Galang Yusuf Pujiyanto; Ibnu Fatkhu Royana; Muh. Isna Nurdin Wibisana (Physical Education and Sports)
Background: The integration of interactive, technology-based media in Physical Education, particularly for teaching health-related content, remains limited despite its potential to enhance student engagement and learning outcomes.